Pertanggungjawaban Pidana Terhadap Penderita Skizofrenia Dalam Hukum Pidana Di Indonesia - Bawazir, Fuad; Sudarti, Elly; Erwin, Erwin (Universitas Muhammadiyah Tapanuli Selatan, 2025)
Indonesia's penal code provides exceptions for individuals diagnosed with mental disorders, such as schizophrenia, which impair their ability to understand or control their actions at the time of committing a crime. The purpose of this study is to analyze the criminal liability of individuals with schizophrenia within the Indonesian criminal justice system, focusing on how mental disorders affect their legal capacity to be accountable for their actions. This research uses a qualitative approach with case studies to examine the criminal liability of individuals with schizophrenia in Indonesia's legal framework. The findings reveal inconsistencies in the application of criminal liability for people with schizophrenia, despite clear legal provisions in Article 44, paragraph (1) of the Criminal Code. Data shows that in many cases, even when the offender has a mental disorder, courts often impose prison sentences or detention, ignoring the potential for more humane and effective medical rehabilitation. The lack of rehabilitation facilities and trained medical personnel further hinders the recovery process for these individuals, who should receive intensive care rather than prison sentences